Establishing Land Suitability Criteria for Cashew (Anacardium occidentale L.) in Indonesia - Widiatmaka; Atang Sutandi; Anas Iswandi; Usman Daras; Muhammad Hikmat; Ari Krisnohadi (Applied and Environmental Soil Science)
Commodity development requires site selection which should be established prior to large scale development. The land suitability criteria for cashew are not presently available. The relationship between the biophysical aspects, especially land and soil with commodity productivity, is also not known in depth. The objective of this study is to establish the criteria of land suitability for cashew in Indonesia, based on its production and land characteristics. Cashew plantations in 5 provinces were sampled. The data of production per tree per year were obtained from farmers, while the soil was sampled and analyzed in the laboratory. Age-adjusted cashew production was used as the yield response and plotted against land characteristics. Boundary lines resulting from the scatter of points were described; these lines produced the limits of land suitability criteria. The criteria were established using a projection of the intersection between the boundary line and yield interval. The criteria were also built in accordance with the productivity index of FAO for the internal boundary inside the S (suitable) class and by calculating the break-event point production for the boundary between S (suitable) and N (nonsuitable) order. The main result of this research is land suitability criteria for cashew.